No social distancing from food: How the COVID-19 pandemic shaped student food-related activities in the Western Balkans - Hassen, Tarek Ben; Bilali, Hamid El; Allahyari, Mohammad S; Berjan, Sinisa; Radosavac, Adriana; Cvijanovic, Drago; Bogevska, Zvezda; Despotovic, Aleksandra; Vaško, Željko (SAGE Publications, 2023)
The COVID-19 pandemic has influenced food preparation and consumption habits, as well as food wastage. The pandemic also affected the lives of university students worldwide; their learning and living environments changed, influencing their eating habits.